Genetic variation in UGT1A1 is not associated with altered liver biochemical parameters in healthy volunteers participating in bioequivalence trials - González-Iglesias, Eva; Ochoa, Dolores; Román, Manuel; Soria-Chacartegui, Paula; Martín-Vilchez, Samuel; Navares-Gómez, Marcos; De Miguel, Alejandro; Zubiaur, Pablo; Rodríguez-Lopez, Andrea; Abad-Santos, Francisco; Novalbos, Jesús (Frontiers in Pharmacology, 2024)
Bioequivalence clinical trials are conducted in healthy volunteers whose blood tests should be within normal limits; individuals with Gilbert syndrome (GS) are excluded from these studies on suspicion of any liver disease, even if the change is clinically insignificant . GS is a benign genetic disorder characterized by elevated bilirubin levels, the primary cause of which is the presence of polymorphisms in UGT1A1 gene. In this work, subjects with UGT1A1 intermediate (IM) or poor (PM) metabolizer genotype-informed phenotypes were investigated to determine whether they have a higher incidence of liver disease or other biochemical parameters. The study population comprised 773 healthy volunteers who underwent biochemical analysis at baseline and at the end of the study which were genotyped for UGT1A1*80 (rs887829), as an indicator of UGT1A1*80+*28 (rs887829 and rs3064744), and UGT1A1*6 (rs4148323). Bilirubin levels were higher in subjects IMs and PMs compared to normal metabolizers (NMs). Decreased uric acid levels was observed in PMs compared to NMs. No associations were observed in liver enzyme levels according to UGT1A1 phenotype. Considering that there is no hepatic toxicity in subjects with UGT1A1 IM or PM phenotype, who are more likely to develop GS, this study suggests that they could be included in bioequivalence clinical trials as their biochemical parameters are not affected outside normal ranges.